Digital Transformation and Employee Productivity in Nigeria’s Mobile Telecommunication Sector - Ezinne Mary Kekeocha; Sunday Peter Oliseh; Victoria Kenechukwu Anagwu; Christian Chidi Nwanya (Annals of Management and Organization Research, 2026)
Purpose: This study seeks to analyze Digital Transformation and employee productivity in Nigeria’s mobile telecommunications sector by specifically examining the effect of digital skills and task efficiency among employees and investigating the effect of technology adoption on the output quality of employees in Nigeria’s mobile telecommunications sector.  Research Methodology: A survey research design was utilized, and data were collected from 347 employees in the Nigerian mobile telecommunications sector and analyzed using linear regression.  Results: The findings revealed that digital skills had a significant, strong positive effect on task efficiency, with the model explaining 61.3% of the variance. Similarly, technology adoption significantly and positively affected output quality, accounting for 45.4% of the variance in the outcome variable. Conclusions: Mobile telecommunication firms must prioritize strategic training initiatives to fully leverage their technological investments and optimize workforce performance Limitations: Online surveys were utilized; hence, there may be bias in responses from respondents. Contributions: This study will enable the management of mobile telecommunications firms to design and implement target programs and provide insight into how to collaborate with policymakers and industry leaders to develop a digital literacy framework.